The Influence Of Leverage, Firm Size And Sales Growth On Financial Performance At Pt Indocement Tunggal Prakarsa Tbk - Selfania, Selfania; Huda, Nurul; Aprianti, Kartin (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to determine and analyze the influence of leverage, firm size and sales growth on the financial performance of PT Indocement Tunggal Prakarsa Tbk. The type of research used is associative research. The research instrument used was tabulating financial report data for 15 years (2008-2022). The population in this study was 18 years (2005-2022). The sample in this research was for 15 years (2008-2022). The sampling technique used was purposive sampling technique. The data analysis techniques used are classical assumption testing, multiple linear regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study indicate that leverage and firm size have a partially significant negative effect on financial performance and sales growth has no effect and is not significant on financial performance, leverage, firm size and sales growth have a significant simultaneous effect on financial performance.